Nothing but a piano-key: populism as a consequence of relational pathology - Dufek, Pavel; Ruzicka, Adam (Frontiers in Political Science, 2025)
The paper examines populism as a symptom of a dysfunctional relationship between the few (elites) and the many (the masses) in liberal democracies. We take as the core broken promise of contemporary liberal democracies the failure to deliver the assurance of there being a meaningful relationship between the citizens' self and the increasingly complex, difficult-to-understand world. Employing Frank's theory of credible commitment, we propose that populism's success lies in its ability to signal commitment through seemingly irrational actions, a strategy which creates trustworthiness on the part of populist leaders but exacerbates generalized distrust in the institutional system. Moreover, the non-populist forms of trust-building find it difficult to compete with such an emotionally loaded appeal. In the latter parts of the paper, we discuss the detrimental effects of the populist way of creating trust on democracy's self-correcting capacities, contending that it engenders its own relational pathologies and ultimately undermines the very system it seeks to correct. Finally, we address populism's disruptive impact on public justification of collectively binding norms and shared institutions. By highlighting the relational dimension of populism, the paper urges a nuanced understanding of populism's appeal as a reaction to, and simultaneously an amplifier of, the pathologies of liberal democracies.